1999
DOI: 10.1021/ma981875p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Polyhedral Silsesquioxanes Bearing Bulky Functionalized Substituents

Abstract: A simple route to synthesize polyhedral silsesquioxanes, (RSiO1.5) n , by the hydrolytic condensation of modified aminosilanes, is reported. The starting material was N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, a trifunctional aminosilane. It was reacted with a stoichiometric amount of phenylglycidyl ether in sealed ampules at 50 °C for 24 h, leading to the trisubstituted product plus a series of oligomers arising from the intermolecular reaction between methoxysilane groups and the secondary hydroxyls gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 21 publications
5
92
0
Order By: Relevance
“…3) and were obtained by a careful choice of the organic group promoting intramolecular cyclization and condensation conditions. Fasce et al reported similar considerations on cage-type silsesquioxanes with 8, 9, and 10 Si atoms, obtained by the hydrolytic condensation of triethoxysilanes with bulky organic substituents (Fasce et al 1999(Fasce et al , 2001. The presence of (β-hydroxyl) tertiary amine functions in the bulky organic group of the pristine organosilane favored the formation of closed structures (Dell'Erba et al 2003;Fasce et al 2005).…”
Section: Acid-catalyzed Synthesis Of Silsesquioxanesmentioning
confidence: 80%
“…3) and were obtained by a careful choice of the organic group promoting intramolecular cyclization and condensation conditions. Fasce et al reported similar considerations on cage-type silsesquioxanes with 8, 9, and 10 Si atoms, obtained by the hydrolytic condensation of triethoxysilanes with bulky organic substituents (Fasce et al 1999(Fasce et al , 2001. The presence of (β-hydroxyl) tertiary amine functions in the bulky organic group of the pristine organosilane favored the formation of closed structures (Dell'Erba et al 2003;Fasce et al 2005).…”
Section: Acid-catalyzed Synthesis Of Silsesquioxanesmentioning
confidence: 80%
“…The structures of the PS-POSS hybrid nanocomposites were well characterized by FTIR, 1 H NMR, and 29 Si NMR, which proved that the resultant nanocomposites were of star and low cross-linking structures. The thermal properties of the PS-POSS hybrid nanocomposites were studied by the DSC and TGA techniques.…”
Section: Discussionmentioning
confidence: 83%
“…The high-resolution 29 Si NMR spectroscopy provides further insight to the copolymerization of styrene with the POSS macromonomers. Figure 4 shows the 29 Si NMR spectra of both pure POSS macromonomer and PS-POSS nanocomposite (2.21 mol % POSS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations